(untitled) (Damu Journal of Sport Sciences, 2024)
The research aims to identify some physical variables and their relationship to measuring the body mass index for overweight people, as an unhealthy lifestyle affects physical changes, which in turn indirectly affects lower back pain. Therefore, following a good healthy lifestyle works to give the individual a healthy and positive life away from pain and makes him able to perform his daily duties with vitality, thus reviving the economic and vital aspect of the individual. Hence the importance of the research in knowing the relationship of physical variables to measuring the body mass index for overweight people because of the effect of this index on physical variables (strength and flexibility). The research sample included (15) homogeneous individuals in the type of injury, suffering from overweight, we are looking for the relationship between some physical variables and the measurement of the body mass index, the research sample was presented to a group of doctors for the purpose of diagnosing the cause of the feeling of pain in the lower back, and it was found that there is a weakness in the balance of the muscles of the region around the lumbar spine. There is a correlation between the physical variables (strength and flexibility) and the body mass index (BMI) for those who are overweight.